2006
DOI: 10.1182/blood-2005-07-2901
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide and cGMP protein kinase (cGK) regulate dendritic-cell migration toward the lymph-node–directing chemokine CCL19

Abstract: Dendritic-cell (DC) migration to secondary lymphoid organs is crucial for the initiation of adaptive immune responses. Although LPS up-regulates CCR7 on DCs, a second signal is required to enable them to migrate toward the chemokine CCL19 (MIP-3␤). We found that the nitric oxide (NO) donor NOR4 provides a signal allowing LPS-stimulated DCs to migrate toward CCL19. NO affects DC migration through both the initial activation of the cGMP/cGMP kinase (cGMP/cGK) pathway and a long-term effect that reduced cGK activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 69 publications
1
34
0
Order By: Relevance
“…NO produced by iNOS in inflammatory monocytes and DC regulates cellular metabolism, inflammatory cytokine production, survival and responsiveness to chemotactic signals. [127][128][129][130] While several reports demonstrate that NO counteracts the expansion of activated CD4…”
Section: Ly6gmentioning
confidence: 99%
“…NO produced by iNOS in inflammatory monocytes and DC regulates cellular metabolism, inflammatory cytokine production, survival and responsiveness to chemotactic signals. [127][128][129][130] While several reports demonstrate that NO counteracts the expansion of activated CD4…”
Section: Ly6gmentioning
confidence: 99%
“…It has been shown that stimulation of PGE 2 receptors EP2 and EP4 is necessary for the function of CCR7 (52,53). Moreover, it also has been shown that LPS-matured DCs only migrate toward the ligand CCL19 in the presence of the free radical gas NO (see below) (54). It is likely that both PGE 2 and NO may regulate the function of CCR7 in the inflammation sites where they are produced (55).…”
Section: Cell Surface Expression Is Not Sufficient For the Functionalmentioning
confidence: 99%
“…The counts fell within a linear range of the control titration curves obtained by testing increasing concentrations of cells. The results are expressed as mean number of migrated cells F SE (67). Unpaired Student's t test was used to determine the differences in migration.…”
Section: Determination Of Cytokine and Chemotaxismentioning
confidence: 99%